MEMBANGUN KEBIASAAN AKTIF BERGERAK MELALUI KEGIATAN SIT LESS MOVE MORE PADA PENDERITA OBESITAS - Iswati Iswati; Alfian Irdhani Mohammad; Putri Sukma Rahayu (Community Development in Health Journal, 2026)
Introduction & Objective: A sedentary lifestyle (lack of movement, lots of sitting/lying down) can increase the risk of heart disease, diabetes, and obesity. Obesity is a global health problem that requires sustainable interventions. This activity aims to build active movement habits in individuals with obesity through the implementation of the "Sit Less, Move More" program. The objective of this activity is to increase active movement behavior through “sit less move more” in individuals with obesity. Implementation Method: Using a Participatory Action Research (PAR) approach with clear and measurable stages. Participants consisted of 22 individuals with obesity who voluntarily joined the program for 9 weeks. Results: showed that knowledge about the dangers of sedentary behavior and the importance of physical activity increased before and after the program, respondents' physical activity changed from mostly moderate activity to high physical activity, and there was a change in BMI from Obesity level II (≥30.0) to Obesity level I (25.0–29.9) in 3 participants. Discussion: The advantage of this program lies in small movements that are easy to integrate into daily routines, which are more sustainable compared to intense exercise that requires additional time and cost, and it teaches that every movement is important, thereby changing the perception that physical activity can only be done through exercise at fitness centers. This program creates collective awareness and social support among participants, which is key to the sustainability of the intervention. It is recommended to continue this program for a longer duration to evaluate long-term impacts, and further research is needed to identify factors influencing the sustainability of healthy behavior after the program ends.